Inter-annual variability and forecast of the spring ice phenomena on Lake Baikal and reservoirs of the Angara cascade - E. N. Sutyrina (Лëд и снег, 2017)
The study of interannual variability of ice phenomena on large inland waters, as well as the ice forecasts for them are of great practical importance for navigation because any ice on water interferes with navigation. This article presents a description of the developed approach to mapping the stages of melting and destruction of ice cover on Lake Baikal, and the Bratsk and Ust-Ilimsk reservoirs using data from AVHRR (Advanced Very High Resolution Radiometer) and shows examples of the ice condition maps in the spring. The AVHRR data, obtained for the period 1998–2015, made possible to analyze processes of the ice disappearance on aquatories of the South, Central and North parts of Lake Baikal, and the Bratsk and Ust'-Ilimsk reservoirs including determination of dates of the total ice disappearance (the first ice-free dates) on the reservoirs under investigation: the average, earliest and latest dates, and a range. It has been found that the interannual changes of these dates are the opposite to the inter-annual fluctuations of values of the Arctic Oscillation (AO) index, that allows using the AO index as a predictor in regional predictive dependencies.Using results of analysis of the AO index values, averaged over different time intervals, and the data series of the first dates of the ice-free situations we constructed regional equations allowing to foresee a character of the ice situation with the average earliness from 21 to 33 days. Tests of effectiveness of the proposed predictive dependencies demonstrated a good quality of forecasts of the dates when Southern, Central and Northern parts of Lake Baikal,as well the Bratsk and Ust-Ilimsk reservoirs become totally free of ice.